2014
DOI: 10.1111/codi.12468
|View full text |Cite
|
Sign up to set email alerts
|

A prospective case controlled study of the short‐term outcome following hemicolectomy for benign compared with malignant colonic polyps

Abstract: Complications following hemicolectomy for BCP or CC are not significantly different. The results of the study provide further impetus to develop local full thickness colonic excision for benign colonic lesions as an alternative to major surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Lastly, our data supports that endoscopic instead of surgical removal of large polyps should be considered first. Surgical removal of large polyps is associated with a considerable level of post-operative complications [ 37 ] and may not be ideal to remove synchronous or metachronous adenomas at multiple sites. In contrast, endoscopic resection allows for repetitive and multilocal removal.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, our data supports that endoscopic instead of surgical removal of large polyps should be considered first. Surgical removal of large polyps is associated with a considerable level of post-operative complications [ 37 ] and may not be ideal to remove synchronous or metachronous adenomas at multiple sites. In contrast, endoscopic resection allows for repetitive and multilocal removal.…”
Section: Discussionmentioning
confidence: 99%
“…Polyp location was the most common reason for referral in three studies, all reporting that the right-sided colon was the most common location for referral [19 -21]. In the other two studies, polyp size was the main reason for referral [18,22], with a median polyp size of 4.0 cm (interquartile range 2.5 -5.4 cm) [22] and a mean polyp size of 3.8 cm (standard deviation 1.9 cm) [18]. Overall, polyp size was reported in 21 of the 26 studies as median, mean, ranges, or categories.…”
Section: Referral Rate and Indications For Surgerymentioning
confidence: 99%
“…2). In studies that used a categorization for polyp size, the majority of the polyps that were referred for surgery were > 2 cm [17, 22 -24], and in the studies that reported on median polyp sizes, sizes ranged from 1.8 cm to 4.0 cm [19,20,22,25] (Table 1s).…”
Section: Referral Rate and Indications For Surgerymentioning
confidence: 99%
“…As mentioned in the introduction, Brigic et al [ 6 ] compared outcomes following segmental colectomy for benign and malignant colonic polyps. The fact that colectomy for benign disease was shown to cause significant morbidity in at least one-third of patients in their study should in their opinion provide further impetus to develop alternative, less invasive treatment options for this growing group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, a more radical mesenteric resection is generally associated with increased morbidity and mortality compared to a smaller resection, and these complications should therefore be weighed against the chance of preventing cancer [ 5 ]. Brigic et al [ 6 ] remarked that clinical outcomes following oncologic resection for benign colonic polyps are poorly documented. Their prospective case controlled study showed similar postoperative complication rates after colonic resections for benign and malignant colonic polyps (46 and 31%, respectively).…”
Section: Introductionmentioning
confidence: 99%